2009
DOI: 10.1080/10439460902871348
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of disparate policing in Indian Country

Abstract: Like most racialised minority groups, Native Americans have long experienced disparate policing, both in the form of over-and under-policing their communities. Inevitably, the interactions between police and Native Americans shape the latter's perceptions of the brand of justice they can expect. Cumulatively, overand under-policing reinforce the antipathy if not outright hostility towards police. They compound the historically strained relationship between Native Americans and the western criminal justice syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…[16][17][18][19]33 Regardless of geographic or neighborhood living situation, Native American adults reported experiencing high levels of discrimination in many areas of life, and our estimates are consistent with nonrepresentative samples that also find discrimination and bias against Native American people in their interactions with the police and the courts. 39,40 This may be due in part to the complex criminal jurisdiction in Indian Country and also racial tension between Native and non-Native communities, including suspicion of law enforcement, perceived prejudice, and cultural conflicts between Native American and Western values. [39][40][41] This study found that more than one in five Native Americans reported avoiding interactions with the legal system because they fear unfair treatment, further perpetuating distrust and increasing racial disparities in interactions with law enforcement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19]33 Regardless of geographic or neighborhood living situation, Native American adults reported experiencing high levels of discrimination in many areas of life, and our estimates are consistent with nonrepresentative samples that also find discrimination and bias against Native American people in their interactions with the police and the courts. 39,40 This may be due in part to the complex criminal jurisdiction in Indian Country and also racial tension between Native and non-Native communities, including suspicion of law enforcement, perceived prejudice, and cultural conflicts between Native American and Western values. [39][40][41] This study found that more than one in five Native Americans reported avoiding interactions with the legal system because they fear unfair treatment, further perpetuating distrust and increasing racial disparities in interactions with law enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 This may be due in part to the complex criminal jurisdiction in Indian Country and also racial tension between Native and non-Native communities, including suspicion of law enforcement, perceived prejudice, and cultural conflicts between Native American and Western values. [39][40][41] This study found that more than one in five Native Americans reported avoiding interactions with the legal system because they fear unfair treatment, further perpetuating distrust and increasing racial disparities in interactions with law enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…Issues of race, social class, and the disparities that result are inherent in the American criminal justice system; however, they may be more pronounced for American Indians. Like other marginalized groups, American Indians are grossly overrepresented at all stages of the criminal justice system (Skoog, 1996), including victimization, arrest, and incarceration (Perry, 2009a). The role of the police in perpetuating these disparities is well documented for other minority groups, namely, African Americans, though less documented for American Indians.…”
Section: Policing American Indian Reservations: Discrimination and VImentioning
confidence: 98%
“…In the research that has been conducted, issues of over-and under-policing are evident across American Indian communities (Perry, 2009a(Perry, , 2009b. For example, Perry (2009a) highlighted the negative perceptions most American Indians have of the police regardless of jurisdiction, including interactions with "tribal and non-tribal, on-and off-reservation, Native and non-Native police officers and agencies" (Perry, 2009a, p. 266). Furthermore, myths about representative police departments-those having comparable racial characteristics to the communities they serve-are also debunked, as previous efforts argued this would deflate tension within racialized communities.…”
Section: Policing American Indian Reservations: Discrimination and VImentioning
confidence: 98%
See 1 more Smart Citation